The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11926-017-0643-y
|View full text |Cite
|
Sign up to set email alerts
|

Managing Cardiovascular Disease Risk in Rheumatoid Arthritis: Clinical Updates and Three Strategic Approaches

Abstract: The increase in cardiovascular disease (CVD) risk in rheumatoid arthritis (RA) is well known; however, appropriate management of this elevated risk in rheumatology clinics is less clear. Purpose of Review By critically reviewing literature published within the past five years, we aim to clarify current knowledge and gaps regarding CVD risk management in RA. Recent Findings We examine recent guidelines, recommendations, and evidence, and discuss three approaches: (1) RA-specific management including treat-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 99 publications
1
32
0
2
Order By: Relevance
“…Cardiovascular disease remains the most common cause of death in RA (28). Large meta-analyses identified an increase of 48% in cardiovascular events and a 50% higher incidence of mortality from cardiovascular causes in RA patients compared to the general population (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular disease remains the most common cause of death in RA (28). Large meta-analyses identified an increase of 48% in cardiovascular events and a 50% higher incidence of mortality from cardiovascular causes in RA patients compared to the general population (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing cardiovascular risk in RA patients may be approached by 3 strategies, as recently proposed by Chodara et al (28): decreasing RA activity, assessing cardiovascular risk using risk calculators, and controlling traditional cardiovascular risk factors. These strategies also form the basis of the "EU-LAR recommendations for cardiovascular disease risk management in patients with RA and other forms of inflammatory joint disorders" (42).…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, у пациентов с ССЗ в бляшках были идентифицированы цитруллированные пептиды, против которых нацелен АЦЦП [15]. Поэтому на сегодняшний день одной из стратегий контроля над сердечно-сосудистым риском при РА -это контроль активности заболевания [9,14]. В эру раннего агрессивного использования синтетических и биологических базисных противовоспалителных препаратов (БПВП), неясно, изначально ли повышена частота кардиоваскулярных событий при РА или же она возрастает в течении заболевания, сопряженная с увеличением синтеза аутоантител.…”
Section: Doiunclassified
“…There are published guidelines for monitoring for CVD in RA (5). Appropriate treatment of RA is an important component of CV risk reduction (6). Studies have also shown improvement in CV health with management of traditional risk factors (4).…”
Section: Introductionmentioning
confidence: 99%